An Association Between Pain and American Association of Respiratory Care 2010 Guidelines During Tracheal Suctioning. Issue 5 (September 2016) - Lucchini, Alberto; Canesi, Marta; Robustelli, Gaia; Fumagalli, Roberto; Bambi, Stefano
Abstract : Introduction: Tracheal suctioning is recalled by mechanically ventilated patients as the most painful procedure during their stay in the intensive care unit. Aim: The aim of this study was to evaluate whether the implementation of American Association of Respiratory Care suction guidelines positively affects the levels of patients' pain. Materials and Methods: This is a prospective observational study on adult patients admitted to 2 general intensive care units. Pain levels in sedated mechanically ventilated patients were recorded before, during, and after tracheal suctioning, using the Critical Care Pain Observation Tool (CPOT). Results: Forty-seven patients were enrolled, with a mean age of 61.72 (±18.46) years. Median CPOT value was 0 (quartile 1 [Q1] [25%], 0; quartile 3 [Q3] [75%], 0; min, 0; max, 2) during the procedure. The Critical Care Pain Observation Tool reached a median value of 3, while 5 minutes after suctioning. Postprocedural CPOT median score was 0 (Q1 [25%], 0; Q3 [75%], 0; min, 0; max, 2). The median number of passes during suctioning was 1 (Q1, 1; Q3, 2). The sizes of suction catheters used in the recorded procedures were as follows: 12F in 27 cases (57%), 14F in 18 cases (38%), and 10F in 2 cases (5%). The median size of the endotracheal tube was 7.5 mm (Q1, 7.5; Q3, 8). The correct ratio between endotracheal tube diameter and suction catheter was used in 24 procedures (51%). Conclusions: Despite the low number of patients, this study showed that the implementation of the American Association of Respiratory Care 2010 endotracheal suctioning guidelines into practice helps to reduce procedural-induced pain. Therefore, training and continuing education are important for clinical staff performing tracheal suctioning.